EVALUASI PELAKSANAAN MUSYAWARAH PERENCANAAN PEMBANGUNAN (MUSRENBANG) KECAMATAN DI KABUPATEN BANJARNEGARA TAHUN 2015 - Lestari, Windy Dwi; Marom, Aufarul (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2017)
Carried out an effective, efficient, and appropiate regional development need an optimal plan that implemented with involved partisipation from the community,so the impact will be appropiate as the need and the demand of community. subdistrict plan development discussion is a subdistrict stakeholder discussion forum to get an input about the priority activity from the village administrator and cross activity to arrange the district's regional plan work in the next year. This research is aimed to investigate the implementation of Subdistrict Plan Development Discussion and to determine what factors that obstruct the implementation. The used method of this research is descriptive qualitative. This research is based on Regional Regulation Number 15 year 2010 about Stages of Control Preparation Procedures and Implementation Evaluation of Regional Plan Development using evaluation indicators by William N. Duun. The research found that the problem of implementation of Subdistrict Plan Development Discussion is; there is a lot of unrealized communities suggestions, Musrenbang only used as an instrument of legitimation, the lack of escorts from the district, lack of trust from the people, and lack of knowledge to understanding the procedure of how to carry out the Subdistrict Plan Development Discussion. recommendation from this Subdistrict Plan Development Discussion research is; the government and thecommunity have to do cooperate in arranging the development plan, consistence with community's suggestions, cooperation and coordination in arrange the development plan, and the need of clear guidelines and mechanisms.